Szalay Sándor – a hazai atommagfizikai alapkutatások elindítója - Fényes, Tibor (Gerundium, 2010)
Sándor Szalay Was the Founder of Basic Research in Nuclear Physics in Hungary. Academian Sándor Szalay, former head of the Department of Experimental Physics at the University of Debrecen as well as the founding director of the Institute of Nuclear Physics of the Hungarian Academy of Sciences (ATOMKI) was born in 1909. He was a trail-blazing physicist, a dedicated teacher, and his achievements in fundamental and applied science are both substantial and diverse. One of his remarkable legacies was the inititation of nuclear physics research in Hungary. On 24 September, 2009, ATOMKI hosted a symposium to mark the centenary of its founder.